DESIGN AND DEVELOPMENT OF A PROJECT TRACKING INFORMATION SYSTEM FOR PT WORLD INNOVATIVE TELECOMMUNICATION BALIKPAPAN - Masria, Masria; Faridl, Miftah; Yasin, Muhammad (ENCRYPTION: Journal of Information And Technology, 2026)
The dynamic management of branding projects at PT World Innovative Telecommunication Balikpapan currently faces significant challenges due to conventional and non-integrated monitoring processes. Disorganized asset data collection and delayed field progress reports lead to information asymmetry, which hinders effective management decision-making. To address these issues, a project tracking information system was developed using the Rapid Application Development (RAD) method. This methodology was selected for its ability to accelerate the development lifecycle through the phases of Requirements Planning, User Design, Construction, and Cutover, while maintaining intensive user involvement. The result of this development is a web-based application built on the Laravel framework, integrating real-time monitoring features, visual documentation validation, and Role-Based Access Control (RBAC). The implementation of this system has proven to enhance coordination transparency across work units, ensure project data accuracy, and optimize the supervisory efficiency of the company's branding activities.